Proteomic analysis of nemaline myopathy in infants reveals distinct common dysregulated proteins and cellular pathways - Hedberg-Oldfors, Carola; Bedir, Ali Zeki; Visuttijai, Kittichate; Michael, Eva; Oldfors, Anders (Frontiers in Neurology, 2025)
BackgroundNemaline myopathy is a rare congenital muscle disorder characterized by the presence of nemaline rods, protein aggregates, in muscle fibers. Pathogenic variants in several genes, most commonly NEB and ACTA1, which encode thin filament proteins of the sarcomere, have been implicated in its etiology. Currently, there is no cure for nemaline myopathy, underscoring the need to identify disease-modifying targets for therapeutic development.MethodsIn this study, we employed quantitative nanoscale liquid chromatography–tandem mass spectrometry (LC-MS3) with labeled protein analysis on muscle tissue from five normal controls and seven infants diagnosed with nemaline myopathy due to NEB or ACTA1 pathogenic variants.ResultsWe identified and quantified 4,846 proteins across all samples, with 183 proteins showing significant dysregulation. Protein–protein interaction analysis revealed nine upregulated, muscle-specific proteins: NRAP, FBXO40, TRIM63, TRIM54, ALPK3, XIRP1, ANKRD2, LMOD2, and CSRP3. Further pathway analysis indicated upregulation of protein synthesis and proteasomal degradation processes, alongside downregulation of glycolysis. Notably, the dysregulated proteins and pathways were consistent across both genetic subtypes, suggesting shared molecular mechanisms underlying the disease.ConclusionThis proteomic profiling study has identified key dysregulated proteins and pathways in infantile nemaline myopathy. These findings advance our understanding of the disease’s molecular basis and highlight candidate targets for future therapeutic intervention.